Phacomorphic Glaucoma as the First Manifestation of the Choroidal Malignant Melanoma - Torabi, Hamidreza Torabi; Daryabari, Seyed Hashem; Naderi, Mostafa (Journal of Ophthalmic and Optometric Sciences, 2017)
Purpose: To describe a case of choroidal melanoma with phacomorphic glaucoma as the first presentation. Case report: A 63-year-old woman was presented with painful visual loss of the left eye. Mature cataract, flat anterior chamber and elevated intraocular pressure were noticed in clinical examination. B mode ultrasonography and CT-Scan showed a large intraocular mass. Enucleation was performed and pathological analysis was compatible with uveal melanoma. Conclusion: The presence of mature cataract obscures the fundus view in patients with phacomorphic glaucoma. Complete ultrasonographic examination or other appropriate imaging techniques should be performed to detect potential posterior segment pathologies like a malignant melanoma among these patients. Keywords: Phacomorphic; Glaucoma; Uveal; Melanoma.